Molecular Docking Analysis of Î±-Tomatine and Tomatidine to Inhibit Epidermal Growth Factor Receptor (EGFR) Activation in Non-Small-Cell Lung Cancer (NSCLC) - Amalia, Intan Fitri; Sayyidah, Assyifa; Larasati, Kirana Aisyah; Budiarti, Sarah Fadilah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2020)
The use of chemical drugs is the most common option for NSCLC therapy but mostly it has side effects,suchasdiarrhea,skinproblems,excessivebodyfeeling,andmouthsores.Therefore,NSCLC therapy using herbal medicine from plant bioactive compound began to be developed to minimize the side effect of chemical drugs consumption. Tomato (Lycopersiconesculentum Mill.) is one of the herbal source which contains bioactive compounds such as Î±-tomatine and tomatidine. The aims of this study is to analyze the effectiveness of Î±-tomatine, tomatidine, and combination of both of them to inhibit EGFR activity by molecular docking. The ligand and protein preparations were done using Discovery Studio 2016 then Hex 8.0.0 is used for docking. Visualization were done using Discovery Studio 2016 as well. Alpha tomatine, tomatidine, and combination of both of them have potential as inhibitors of the interaction between EGFR and EGF as native ligands.Â Combination alpha tomatine and timitidine have the best results among other complex that has been tested with thread of alpha tomatine applied before tomatidine.Â Alpha tomatine and tomatidine can be considered as drugs that can control overexpression of EGFR and decrease activation of one of the lung cancer signaling pathways.Â